The Correlation Between Efl Student`S Attitude And Their Learning Achievement - Putri, Melia; Riza, Armilia; Asty, Herfyna (Jurnal Ilmiah Mandala Education (JIME), 2023)
The study aims to determine whether or not there is a correlation between students' attitudes in learning English and students' learning achievement at SMA Negeri 1 X Koto Tanah Datar Regency. The study population was class x students, totaling 171 students from 5 classes. The sample was taken using simple random sampling technique so that a sample of 50 students was obtained. Data collection techniques using questionnaires and documentation, then analyzed using the Product Moment Correlation formula. The results showed that students had a positive attitude towards learning English with the results of descriptive analysis showing an average score of 75,6. The correlation coefficient of student attitude and student learning achievement was obtained as rxy = 0,232 with a weak correlation level. Then the result is compared with r table df = n-2 significant level of 5% is 0,284 (0,232 < 0,284), the significant r value that has been obtained in the table is 0,053 where 0,053 > 0,05. After conducting the t test, the value of t count = 1,651 is compared with t table = 1,677 for a significant level (α) of 0,05 and df = n-2. This means that r count < r table and t count < t table, which means H0 is accepted and H1 is rejected. Thus the researchers concludes that there is no correlation between students' attitudes and learning achievement in students' English learning at SMA Negeri 1 X Koto Tanah Datar Regency.